2012
DOI: 10.1371/journal.pone.0052985
|View full text |Cite
|
Sign up to set email alerts
|

The Clinically-tested S1P Receptor Agonists, FTY720 and BAF312, Demonstrate Subtype-Specific Bradycardia (S1P1) and Hypertension (S1P3) in Rat

Abstract: Sphingosine-1-phospate (S1P) and S1P receptor agonists elicit mechanism-based effects on cardiovascular function in vivo. Indeed, FTY720 (non-selective S1PX receptor agonist) produces modest hypertension in patients (2–3 mmHg in 1-yr trial) as well as acute bradycardia independent of changes in blood pressure. However, the precise receptor subtypes responsible is controversial, likely dependent upon the cardiovascular response in question (e.g. bradycardia, hypertension), and perhaps even species-dependent sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 40 publications
3
59
0
5
Order By: Relevance
“…The CNS is therefore an important site for mechanism of action of not only FTY720 but also of other S1PR 1 modulators, including CYM-5442 (6,57,71). In our studies, the maximal efficacy regarding the reduction of mechano-hypersensitivity was detected with doses of FTY720 at least 10-fold lower than those shown to cause lymphopenia (6) or bradycardia (72) and for NIBR-14/15 to cause pulmonary vascular leakage (40). Furthermore, we did not observe any changes in differential white blood cell counts following a 6-day infusion of FTY720 that provided near-tomaximal inhibition of CIPN.…”
Section: Discussionmentioning
confidence: 46%
“…The CNS is therefore an important site for mechanism of action of not only FTY720 but also of other S1PR 1 modulators, including CYM-5442 (6,57,71). In our studies, the maximal efficacy regarding the reduction of mechano-hypersensitivity was detected with doses of FTY720 at least 10-fold lower than those shown to cause lymphopenia (6) or bradycardia (72) and for NIBR-14/15 to cause pulmonary vascular leakage (40). Furthermore, we did not observe any changes in differential white blood cell counts following a 6-day infusion of FTY720 that provided near-tomaximal inhibition of CIPN.…”
Section: Discussionmentioning
confidence: 46%
“…This promiscuity may be responsible for adverse affects, such as acute bradycardia (decreased heart rate) and hypertension, seen in fi ngolimod-treated patients ( 32,33 ). Initial results from rodent studies indicated that FTY720 phosphate activation of S1P 3 was responsible for both bradycardia and hypertension; however, treatment of humans with more selective agonists indicated that S1P 1 agonism was responsible for reduced heart rate, whereas S1P 3 signaling contributed to the development of hypertension (34)(35)(36)(37). The divergent utilization of S1P 1 and S1P 3 in rodents versus primates for the regulation of these coordinated .…”
Section: Vascular and Lymphatic Systemsmentioning
confidence: 99%
“…The phosphorylated (active) form of fingolimod was administered at doses of 0.10, 0.30, and 1.00 mg/kg per 30 minutes, and inhibitor 31 was administered at doses of 0.18, 0.61, and 1.8 mg/kg per 30 minutes. The fingolimod doses were selected from published results in a similar model (Fryer et al, 2012), and the doses for inhibitor 31 were selected to achieve blood concentrations that demonstrated pharmacologic activity by reducing lymphocytes (see Results).…”
Section: Methodsmentioning
confidence: 99%
“…Significant reduction in HR was observed with the 0.1, 0.3, and 1.0 mg/kg doses, and no fingolimod phosphate-related changes in MAP were observed. This demonstrates the model is sensitive to the well-characterized reduction in HR from fingolimod-phosphate treatment (Fryer et al, 2012).…”
mentioning
confidence: 94%
See 1 more Smart Citation